ANTHOCYANIN EXTRACTION FROM BLACK RICE AND ROSELLA AS DYE FOR DYE-SENSITIZED SOLAR CELLS (DSSC) - FEBRIANTI (NIM : 20514041), DIANA
The energy consumption has a linier value with the population increasment. Fuel energy used as a primary energy source was decreased because they could not replace. Therefore, alternative energy source is needed. One of the alternative energy sources is a Dye-sensitized Solar Cells (DSSC). DSSC consists of several main components, such as photoanode, counter electrode, dye, and electrolyte. One of the commond dye that used in DSSC is ruthenium complex. The efficiency of ruthenium is more than 10%, but the ruthenium complex is a rare earth metal. Ruthenium is expensive and contain heavy metals that can pollute the environment. Therefore, we need another dye as an alternative to replace the ruthenium complex compound. The alternative dye is anthocyanin. Anthocyanins, a group of flavonoid found in fruits, leaves, and flowers, are water soluble plant pigment. Anthocyanins have vivid colors ranging from red to blue depending on pH and they can be used as antioxidants. Anthocyanins are metal-free compound, nontoxic, and low cost. They also have carbonyl (C=O) and hydroxyl (OH) group that can bind with TiO2 nanocrystal. In this study, anthocyanin was extracted from black rice and rosella. The main type of anthocyanins contained in the black rice and rosella is sianidin-3-glucoside. DSSC performance was optimized by varied of the dye solution concentration, immersion time, and photoanode temperature after impregnation. Pigment concentration is equivalent to cyanidin-3-glucoside. It was calculated using the Lambert Beer equation (A = ɛbc) and the concentration of the dye from black rice and Rosella concentrated solution obtained was 1.5 mM. Dye concentration was varied at 0.01, 0.05, 0.1, 0.5, 1, and 1.5 mM impregnation time was varied at 6, 13, 20, 27, 34, 41, and 48 hours while heat treatment was varied at -6, 25, 40, 60, 80, and 100 oC. The performance of DSSC used solar simulator. The quality of performance is determined by efficiency value. The optymum efficiency value was 0.0739% from black rice dye and 0.1179% from rosella dye with concentration 0,05 mM. The 20h impregnation time resulted optymum efficiency 0.0836% using the black rice dye and 0.1356% using a rosella dye. While the temperature variation of photoanode resulted optymum efficiency at temperature 40 Ã‚Â°C, with an efficiency 0.1110% using the black rice dye and 0.1608% using a Rosella dye. The comparison of ruthenium complex dye with cis-di(thiocyanate)bis(2,2'bipiridil 4,4'-dicarboxylic acid) ruthenium (II) compound or N719 have the same optymum condition as black rice and rosella dye with the dye concentration was 0,05 mM, impregnation time was 20h, and the heating temperature of photoanode was 40 Ã‚Â°C to produced an efficiency 2.2266%.